Freedom of Expression in International Law - Marashini, Sashi Nath (Communication Journal, 2022)
The right to freedom of opinion and expression has been protected in all relevant international human rights treaties since its inclusion in Article 19 of the Universal Declaration of Human Rights. It is essential at an individual level, as it contributes to the overall development of a person and is a foundation stone of democratic society. However, there is a global trend of governments limiting vibrant discussions and debates within civil society and among civil societies, political leaders and governments. This is particularly concerning in western democracies like the USA and UK.